Recruitment of renal functional reserve by intravenous amino acid loading in a sheep model of cardiopulmonary bypass - Taku Furukawa; Alemayehu H. Jufar; Clive N. May; Roger G. Evans; Andrew D. Cochrane; Bruno Marino; Peter R. McCall; Sally G. Hood; Ian E. Birchall; Jaishankar Raman; Pei Chen Connie Ow; Anton Trask-Marino; et al. (Intensive Care Medicine Experimental)
Abstract Background Cardiopulmonary bypass (CPB) may decrease the renal functional reserve (RFR). However, the temporal changes in RFR after during the recovery period after CPB remains unknown. We assessed RFR before and then weekly after CPB over four weeks following CPB in non-anaesthetised sheep. Methods In 10 Merino ewes, amino acids were infused before CPB and weekly for four weeks to assess RFR. At each assessment, we measured renal blood flow (RBF), renal oxygen delivery (RDO2), creatinine clearance and medullary and cortical oxygenation. Histological assessment was performed at 4 weeks. Results Before CPB, amino acid infusion increased RBF from (mean ± SD) 6.60 ± 1.64 to 8.56 ± 1.80 mL/kg/min, and RDO2 from 0.80 ± 0.28 to 1.12 ± 0.37 mL O2/kg/min. These renal macro-circulatory responses remained consistent across all weekly assessments after CPB. Amino acid infusion also increased creatinine clearance (from 62.5 ± 15.0 to 110 ± 30.6 mL/h pre-CPB) throughout the study period. RFR remained unchanged over time (P = 0.53). However, compared with pre-CPB values, medullary (33.9 ± 9.0 pre-CPB to 15.1 ± 13.2 mmHg at 4 weeks, P = 0.0068) and cortical tissue PO2 (46.0 ± 14.2 to 17.2 ± 6.5 mmHg, P = 0.0029) decreased over time. Furthermore, the response of the medullary (but not cortical) PO₂ to amino acid infusion changed over time (P = 0.0064). While medullary PO₂ did not change in response to amino acid infusion pre-CPB and at one week after CPB, it appeared to fall from two weeks thereafter (P = 0.039 and 0.091 at weeks 2 and 3, respectively). Despite preserved RFR, sheep exposed to CPB showed greater peritubular inflammation, interstitial fibrosis and tubular casts compared with healthy controls (P = 0.007, 0.021, 0.007, respectively). Conclusions In this large mammalian model of CPB, weekly amino acid administration consistently recruited RFR over four weeks, despite the presence of histological injury. However, it was associated with the development of renal medullary hypoxia after two weeks. These findings highlight the complexity of the pathophysiological response of the kidney to CPB.